KOMPOSISI KIMIA IKAN TERI (Stolephorus sp.) ASIN YANG DIPASARKAN DI KOTA KENDARI PROVINSI SULAWESI TENGGARA - Waode Nilda Arifiana Effendy; Laode Muhamad Hazairin Nadia; Nurhuda Annaastasia; La Ode Huli; La Ode Abdul Fajar Hasidu (Jurnal Fish Protech, 2023)
This study aims to determine the chemical composition of salted anchovies (Stolephorus sp.) were sold in 6 markets and 1 supermarket in Kendari City, Southeast Sulawesi Province. Parameters observed were chemical composition (moisture content, ash content, protein content and fat content). Data analysis in this study was descriptive with the aim to obtain an objective explanation of the test parameters.. The results showed that the water content of salted anchovies ranged from 17.85% -28.19%. Ash content ranged from 8.14% -14.93%, protein content was 24.41% -31.42% and fat content was 1.02% -1.26%. The results of this study provide information that the salted anchovies marketed in 6 markets and               1 supermarket in Kendari City, Southeast Sulawesi Province have different chemical compositions.Keywords: salted anchovy (Stolephorus sp.), chemical composition, market